Successful removal of giant mediastinal lipoma and liposarcoma involving both chest cavities: Two case reports. Issue 32 (August 2018) - Chen, Chen; Chen, Mingjiu; Liu, Wenliang; Yuan, Yunchang; Yu, Fenglei
Abstract: Rationale: Surgical removal of a giant mediastinal lipoma or liposarcoma involving both chest cavities is always challenging. Patient concerns: We present 2 cases of giant mediastinal tumor, one of which was a 22-year-old female who was admitted to our hospital due to a mild dyspnea after running. Computed tomography (CT) scan revealed a large mass with low density occupying the entire right hemithorax and extending anteriorly into the left. The other patient was a 43-year-old male, who was presented to the hospital with complaints of gradually progressive dyspnea. CT scan revealed a mass comprised of fat density with areas of soft-tissue density in-between, involving in both chest cavities, draping around the heart and great vessels. Interventions: Both of the patients receive complete resection through a standard median sternotomy. Diagnoses: Histologic examination revealed lipoma for the first patient, and well differentiated liposarcoma for the second. Outcomes: Both of their symptoms were improved after surgery and the postoperative courses were good. Lessons: Our experience indicated that complete surgical removal through a standard median sternotomy is a safe and efficient approach for the treatment of giant mediastinal lipoma and liposarcoma.